Complete mitochondrial genome of a DHA-rich protist Schizochytrium sp. TIO1101. Issue 1 (1st January 2016) - Wang, Zhaokai; Lou, Sulin; Hu, Fan; Wu, Peng; Yang, Longhe; Li, Huanqin; He, Lijuan; Lin, Xiangzhi
Abstract: Schizochytrium sp. TIO1101 is a crucial commercial alga used to produce docosahexaenoic acid (DHA), a long-chain polyunsaturated fatty acid that is beneficial for human health. In this study, we sequenced the mitochondrial genome (mitogenome) of Schizochytrium sp. TIO1101 for the first time using an Illumina HiSeq 2500 system (Illumina Inc., San Deigo, CA). The assembled mitogenome was 31 494 bp long with 33.92% GC content. The mitogenome contains 56 genes, including 33 protein-coding genes, 21 transfer RNA genes and two ribosomal RNA genes. Maximum-likelihood phylogenetic analysis of Schizochytrium sp. TIO1101 showed that it was most closely related to Thraustochytrium aureum among the examined species.